Effect of cilomilast (Ariflo) on TNF-α, IL-8, and GM-CSF release by airway cells of patients with COPD. Issue 7 (1st July 2003) - Profita, M; Chiappara, G; Mirabella, F; Di Giorgi, R; Chimenti, L; Costanzo, G; Riccobono, L; Bellia, V; Bousquet, J; Vignola, A M
Abstract : Background: Inflammation in chronic obstructive pulmonary disease (COPD) is characterised by increased neutrophilic infiltration of the airways. Cilomilast, a novel selective phosphodiesterase 4 inhibitor in clinical development for COPD treatment, exerts anti-inflammatory effects. The ability of cilomilast to inhibit the release of neutrophil chemoattractants such as tumour necrosis factor (TNF)-α, interleukin (IL)-8, and granulocyte-macrophage colony stimulating factor (GM-CSF) by bronchial epithelial cells and sputum cells isolated from 10 patients with COPD, 14 normal controls, and 10 smokers was investigated. Methods: Bronchial epithelial cells obtained by bronchial brushing and sputum cells isolated from induced sputum samples were cultured for 24 hours in the presence or absence of cilomilast (1 μM). After incubation the supernatants were harvested and the levels of mediators measured by ELISA. Chemotactic activity in supernatants was also measured using a Boyden chamber. Results: TNF-α and IL-8 release by bronchial epithelial cells and sputum cells was higher in patients with COPD than in controls (p<0.0001) and smokers (p<0.0001). GM-CSF was only detectable in sputum cell supernatants and its level was higher in patients with COPD than in controls and smokers (p<0.0001, respectively). Cilomilast significantly reduced TNF-α release by bronchial epithelial cells and sputum cells (p=0.005) and GM-CSF release by sputum cells (p=0.003), whereas IL-8 release was not statistically inhibited. Supernatants of sputum cells and bronchial epithelial cells treated with cilomilast significantly decreased neutrophil chemotaxis (p<0.006 and p<0.008, respectively). Conclusions: Cilomilast inhibits the production of some neutrophil chemoattractants by airway cells. This drug may play a role in the resolution of neutrophilic inflammation associated with COPD and cigarette smoke.